When a Calling Goes Unanswered: Exploring the Role of Workplace Personalizations as Calling Enactments - Felix, Bruno; Cavazotte, Flavia (Frontiers in Psychology, 2019)
Individuals are sometimes unable to realize their callings in their formal careers. The literature has highlighted that such unanswered callings produce negative outcomes in the individual's career and personal life and that coping strategies, such as job and leisure, can help them buffer such consequences. We developed a grounded theory regarding how people cope with their unanswered callings through a previously unexplored strategy in the calling literature: workplace personalization. Our study revealed that through this strategy, individuals retain the aspects of an unanswered calling in their self-concept and then reduce the consequences of not realizing the calling. Some participants enjoy some of the benefits of perceiving a calling, even without performing it in a formal work role. This phenomenon occurs because workplace personalization can be used to represent unanswered callings performed in the past and present that are intended to be performed in the future. This form of enactment produces interpersonal and intrapersonal processes that helps buffer the negative consequences of not realizing a calling.